Poder político, território e crise ambiental na Colômbia - Bermúdez, Oscar Buitrago; Leal, Antonio Cezar [UNESP] (My University, 2012)
Political power, territory and environmental crisis in Colombia. We describe some forms of operation of the political power of the Colombian State and their impacts on the territory. The analysis uses some results of a doctoral research that sought to understand the institutional and regulatory foundations and the water management practices in two metropolitan areas of South America, Cali in Colombia, and Campinas in Brazil. The theoretical framework, primarily based on critical thought, starts by making an approach to the concept of power and then links it with the concepts of territory and governance. We present empirical evidence on how the political power of the Colombian State operates on the environmental institutional structure. We concluded that the authoritarian interference of the executive power has generated crisis on the institutional framework and facilitated the advancement of the neo-liberal capitalist model.
Political power, territory and environmental crisis in Colombia
Keywords: Authoritarian governance; Colombia; Environmental institutional crisis